Overexpression of circular RNA circ‐CDC45 facilitates glioma cell progression by sponging miR‐516b and miR‐527 and predicts an adverse prognosis. Issue 1 (12th August 2019) - Liu, Jie; Hou, Kuiyuan; Ji, Hang; Mi, Shan; Yu, Guangna; Hu, Shaoshan; Wang, Jianjiao
Abstract: Glioma (GM) is a highly lethal human cancer. Circular RNAs (circRNAs) act as an imperative factor in oncogenesis. We aimed to investigate the biological functions and mechanisms of circ‐CDC45 in GM. circ‐CDC45 expression in GM specimens and cell lines was measured by real‐time quantitative reverse transcription polymerase chain reaction. Fisher's exact test and Kaplan‐Meier curves further analyzed its clinical implications. A gain/loss‐of‐function study was conducted to investigate the role of circ‐CDC45 in GM. Additionally, luciferase reporter and rescue assays were performed to unravel the mechanisms of circ‐CDC45. High circ‐CDC45 expression was found in GM specimens and cells, which was tightly related to a larger tumor size, higher world health organization (WHO) stages, and worse survival for patients with GM. Functionally, manipulation of circ‐CDC45 expression strongly affected cell growth, apoptosis, migration and invasion, which suggests the oncogenic function of circ‐CDC45 in GM oncogenesis. Stepwise mechanism studies indicated that circ‐CDC45 sponged and regulated the expression of miR‐516b and miR‐527 to promote cell growth and invasion. Briefly, the regulatory network of circ‐CDC45/miR‐516b/miR‐527 plays a pivotal role in GM tumorigenesis and may act as a potential target for GM treatment. Abstract : Upregulated circ‐CDC45 is related to poor prognosis in glioma (GM) patients. circ‐CDC45 could sponge miR‐516b and miR‐527. The oncogenic functions of circ‐CDC45 is dependent on its regulation of miR‐516b and miR‐527.